Royal jelly as a novel bio-stimulant for asymbiotic seed germination andprotocorm development in Phalaenopsis - Bidarnamani, Fatemeh (Journal of Horticultural Sciences, 2025)
Orchid micropropagation is often limited by slow seed germination and early seedling development. This study evaluated the potential of royal jelly (RJ), a nutrient-rich organic substance, as a growth-promoting additive in the asymbiotic culture of five Phalaenopsis varieties viz., Nottingham, Dubrovnik, Andorra, Memphis, and Bucharest. A factorial experiment was conducted using two peptone concentrations (1/ gL{ 1 and 2/ gL{ 1) combined with four RJ levels (0, 150, 300, and 450/ ppm) in half-strength Murashige and Skoog (MS) medium. Results demonstrated that RJ significantly enhanced germination and seedling development in a concentration- dependent manner. The variety Nottingham cultured in 2/ gL{ 1 peptone medium supplemented with 300/ ppm RJ achieved the highest germination rate of 96.33%, reduced the time to protocorm formation by 2–3/ days, and increased leaf and root primordia numbers by 15–20% compared with the control. Higher RJ concentrations (450/ ppm) occasionally reduced germination and delayed early growth, indicating an optimal range for supplementation. These findings suggest that RJ can serve as an effective organic bio-stimulant for Phalaenopsis micropropagation, offering a sustainable alternative to conventional synthetic growth regulators. Future studies should isolate active compounds in RJ and assess its scalability across different orchid species.
Keywords: bio-stimulant; micropropagation; organic; Phalaenopsis; protocorm development; royal jelly; seed germination